Efektivitas Perlindungan Hukum Notaris melalui Majelis Kehormatan Notaris dalam Perkara Perdata - Alma pera; Azkia Nabila (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
A notary, as a public official, is authorized to create authentic deeds that serve as perfect evidence in civil law. In carrying out their duties, notaries may face lawsuits or legal proceedings related to the deeds they have executed. To provide legal protection in the performance of notarial duties, the Notary Position Act establishes the Notary Honorary Council (Majelis Kehormatan Notaris/MKN), which has the authority to grant or deny requests from investigators, public prosecutors, or judges concerning the summoning of notaries and the examination of deed protocols. This study aims to analyze the effectiveness of legal protection provided to notaries through the Notary Honorary Council in civil litigation and to identify the factors affecting the effectiveness of such protection. The research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that the existence of the Notary Honorary Council provides both preventive and repressive legal protection for notaries in the exercise of their professional duties. However, the effectiveness of such protection still faces several challenges, including differing interpretations of the Council’s authority, limited understanding among parties regarding the scope of notarial liability and suboptimal coordination among law enforcement institutions. Therefore, strengthening the regulatory framework and enhancing legal awareness are necessary to ensure legal certainty, protect the notarial profession and maintain a balance between law enforcement interests and the proper execution of notarial duties.